FAMILIES OF CHILDREN WITH DEVELOPMENTAL DISABILITIES: PERCEPTIONS AND EXPERIENCES OF ADOLESCENT SIBLINGS OF CHILDREN WITH DEVELOPMENTAL DISABILITIES - Dervishaliaj, Erjona; Murati, Elediona (European Scientific Journal, ESJ, 2014)
Parents of children with developmental disabilities often report increased stress compared to parents of children with typically developing children (Yazigi, & Mooney, 2005). Hence, there has been interest in whether some siblings in a family environment that includes a child with a developmental disability, and possibly a parent under considerable stress, might also be at risk for adjustment difficulties. In terms of how siblings adjust to living and growing up with a brother or sister with developing disabilities, there are mixed findings in other countries, whether there are few studies done in Albania. Some researchers report that children with a brother or sister with developmental disabilities are at a higher risk for internalizing and externalizing behavior problems ( Fisman, Wolf, Ellison, & Freeman, 2000; Hastings,2003) and for impoverished sibling and peer developing children. The aim of the study is to explore perceptions and experiences of siblings who have a brother or sister with developmental disabilities. Method: Semistructured interviews were used with seven typically developing siblings (age 10-16) who have e brother/sister with a developmental disabilities. Unstructured observation of siblings’ interaction were made to better support findings. Also, subjects were asked to keep a diary on their every day relationship with their sibings. Importance of the study: Since there is little research done on this topic, we hope that exploratory findings will help professionals to a better understanding on what happens to adjustment and coping mechanisms in siblings of children with developmental disabilities. Also, we hope that findings will help enhancing the development of support services for siblings of children with developmental disability.